Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1589/jpts.25.1629
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Scoliosis Angle on Center of Gravity Sway

Abstract: [Purpose] The purpose of this study was to verify the effects of idiopathic scoliosis on the human body by comparing the postural balance of adolescents with and without idiopathic scoliosis, to provide basic data for the optimal desirable growth and development of adolescents. [Subjects] The subjects were 128 adolescents diagnosed with scoliosis on X-ray by orthopedists. The subjects were divided into a 10 to 19 degree group, 20 to 29 degree group, and 30 degree and over group according to the degree of scoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 8 publications
3
18
1
Order By: Relevance
“…No signi cant di erence between scoliotic girls and the controls during double stance was revealed. is nding can be considered surprising in view of other studies which report decreased stability in girls with scoliosis [6,9,[12][13][14][15][16][17][18][19]. In those studies, the angle of curvature was smaller (27 ± 6° [6]; 27.2 ± 12.4° [9]; 29.4 ± 9.4° [13]; 13.5 ± 5.5° [14], respectively) comparing to this study (41.7 ± 17.4°).…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…No signi cant di erence between scoliotic girls and the controls during double stance was revealed. is nding can be considered surprising in view of other studies which report decreased stability in girls with scoliosis [6,9,[12][13][14][15][16][17][18][19]. In those studies, the angle of curvature was smaller (27 ± 6° [6]; 27.2 ± 12.4° [9]; 29.4 ± 9.4° [13]; 13.5 ± 5.5° [14], respectively) comparing to this study (41.7 ± 17.4°).…”
Section: Discussioncontrasting
confidence: 96%
“…However, the groups of healthy and scoliotic girls were matched by weight but not by age, height, and BMI as they were in this study [13]. Park et al (2013) revealed that comparing to healthy controls, the scoliotic teenagers revealed worse postural stability under visual control [19]. at study endorsed di erent methodology, since the participants were asked to shi their body to the speci c targets under visual control while in this study the subjects were instructed to look straight ahead during quiet standing task [16].…”
Section: Discussionmentioning
confidence: 98%
“…In other words, this function stabilizes the line of gravity in the entire body by aligning the body based on its external environment 27 , 28 , 29 ) . Morphological changes and a damaged sense of movement, which are related to idiopathic scoliosis, cause problems with balance control 30 , 31 ) . Therefore, exercises may be essential for improving neuromotor control, the stability of physical balance, and respiratory functions 32 , 33 ) .…”
Section: Discussionmentioning
confidence: 99%
“…He found considerable differences between groups; the mean parameters of dynamic balance were worse in girls with hyperkyphosis. In recent years, many researchers have been engaged in posturographic studies in lateral curvatures of the spine (Bruyneel, Chavet, Bollini & Mesure, 2010;Gruber et al, 2011;de Abreu et al, 2012;de Santiago et al, 2013;Park et al, 2013). These researchers indicated significant relationships between balance reactions and postural defects (Pasha et al, 2014;Catanzariti et al, 2014;Gur et al, 2015;Nishida et al, 2016).…”
Section: Resultsmentioning
confidence: 99%